THE RELATIONSHIP BETWEEN INTENSITY OF SOCIAL MEDIA USE AND QUALITY OF SLEEP IN ADOLESCENTS AT SMP N 1 JUWIRING - Alya Dyah Permatasari Permatasari; Anik Suwarni; Sutrisno Sutrisno; Atik Aryani (Universitas Sahid Surakarta, 2023)
Teenagers spend a lot of time on social media. Social media is a digital medium for interaction. Social media is an online media with many users around the world. Social media is used to share information and participate. Indonesia's social media users reach 130 million, or 56% of the total population. The use of social media can interfere with sleep quality so that sleep patterns become worse. It is due to sleep must be without the burden of thought. However, social media users still ignore notifications from smartphones and interact with social media for a long time so that it can affect sleep quality. Objectives: To determine the correlation between the intensity of social media use and the quality of sleep in adolescents in government junior high school (SMPN) 1 Juwiring. The research is descriptive correlational. The research design is crosssectional. The population were 255 grade 8 teenagers at SMPN I Juwiring. The sampling technique used purposive sampling. The social media instrument uses a questionnaire and sleep quality uses the PSQI. Data analysis used the Kendall tau test. Results: The age characteristics of the 72 respondents show that the majority were 13 years old with 53 people (73.3%) and the most gender was female with 36 people (50%). The most intense use of social media is high with 39 people (53.3%). The value of the influence of the intensity of social media on sleep quality shows a correlation value of Kendall tau 0,283. Conclusion: There is a correlation between social media intensity and sleep quality at SMPN 1 Juwiring with a p value = 0,022. Keywords: Intensity, Social Media, Sleep Quality